Precipitation Extremes and Their Links with Regional and Local Temperatures: A Case Study over the Ottawa River Basin, Canada - Llerena, Ana; Gachon, Philippe; Laprise, René (Atmosphere, 2023)
In the context of global warming, the Clausius–Clapeyron (CC) relationship has been widely used as an indicator of the evolution of the precipitation regime, including daily and sub-daily extremes. This study aims to verify the existence of links between precipitation extremes and 2 m air temperature for the Ottawa River Basin (ORB, Canada) over the period 1981–2010, applying an exponential relationship between the 99th percentile of precipitation and temperature characteristics. Three simulations of the Canadian Regional Climate Model version 5 (CRCM5), at three different resolutions (0.44°, 0.22°, and 0.11°), one simulation using the recent CRCM version 6 (CRCM6) at “convection-permitting” resolution (2.5 km), and two reanalysis products (ERA5 and ERA5-Land) were used to investigate the CC scaling hypothesis that precipitation increases at the same rate as the atmospheric moisture-holding capacity (i.e., 6.8%/°C). In general, daily precipitation follows a lower rate of change than the CC scaling with median values between 2 and 4%/°C for the ORB and with a level of statistical significance of 5%, while hourly precipitation increases faster with temperature, between 4 and 7%/°C. In the latter case, rates of change greater than the CC scaling were even up to 10.2%/°C for the simulation at 0.11°. A hook shape is observed in summer for CRCM5 simulations, near the 20–25 °C temperature threshold, where the 99th percentile of precipitation decreases with temperature, especially at higher resolution with the CRCM6 data. Beyond the threshold of 20 °C, it appears that the atmospheric moisture-holding capacity is not the only determining factor for generating precipitation extremes. Other factors need to be considered, such as the moisture availability at the time of the precipitation event, and the presence of dynamical mechanisms that increase, for example, upward vertical motion. As mentioned in previous studies, the applicability of the CC scaling should not be generalised in the study of precipitation extremes. The time and spatial scales and season are also dependent factors that must be taken into account. In fact, the evolution of precipitation extremes and temperature relationships should be identified and evaluated with very high spatial resolution simulations, knowing that local temperature and regional physiographic features play a major role in the occurrence and intensity of precipitation extremes. As precipitation extremes have important effects on the occurrence of floods with potential deleterious damages, further research needs to explore the sensitivity of projections to resolution with various air temperature and humidity thresholds, especially at the sub-daily scale, as these precipitation types seem to increase faster with temperature than with daily-scale values. This will help to develop decision-making and adaptation strategies based on improved physical knowledge or approaches and not on a single assumption based on CC scaling.
Keywords: Gachon_Philippe; Infolettre; Infolettre_Ete_2023; Infolettre_Septembre_2023; Site_internet_RIISQ

Analyse des liens entre la précipitation extrême et la température : étude de cas dans le bassin versant de la rivière des Outaouais (BVRO) à partir des simulations du modèle climatique régional développé au centre ESCER - Llerena, Ana (2021)
Dans le contexte du réchauffement planétaire, la relation de Clausius Clapeyron (CC) est utilisée comme un indicateur de l’évolution des précipitations extrêmes. Parmi les théories proposées, nous utilisons dans notre recherche une relation exponentielle qui fait le lien entre l’évolution des centiles les plus extrêmes des précipitations et le changement de la température ΔT dans le climat actuel. Selon cette théorie, les précipitations augmentent au même rythme que la capacité de rétention d'humidité dans l’atmosphère, expliquée par la relation de CC, avec un taux de changement d'environ 7 % par degré Celsius pour des valeurs de température et de pression près de la surface. Ainsi, le présent travail vise à vérifier l’existence de liens physiquement plausibles dans la relation entre les précipitations extrêmes et la température de l’air pour la région du Bassin Versant de la Rivière des Outaouais (BVRO) sur la période 1981-2010, à l’aide des simulations du Modèle Régional Canadien du Climat (MRCC) (versions 5 et 6), développé au centre ESCER, et de deux produits de réanalyses du Centre Européen pour les prévisions météorologiques à moyen terme (CEPMMT) à différentes résolutions spatiales. En général, les précipitations quotidiennes suivent un taux de changement inférieur à celui de CC ; tandis que les précipitations horaires augmentent plus rapidement avec la température. Dans ce dernier cas, pour la simulation du MRCC5 à plus haute résolution spatiale, des taux de changement supérieurs à CC ont même été produits, jusqu’à 10,2 %/°C. Ce travail a également mis en évidence qu’au-delà du seuil de 20°C, la capacité de rétention d'humidité de l’atmosphère n’est pas le seul facteur déterminant pour générer des précipitations extrêmes, et que d’autres facteurs sont à considérer, comme la disponibilité de l'humidité au moment de l'événement de précipitation et la présence de mécanismes dynamiques qui favorisent les mouvements verticaux ascendants. Un comportement sous forme de crochet, qui décrit une augmentation des précipitations jusqu'à un seuil de température, est observé dans la saison estivale avec le MRCC5, mais il a disparu avec les simulations du MRCC6, ce qui pourrait être une conséquence d’avoir seulement une année de simulation disponible ou bien d’une conséquence de la très haute résolution du modèle sur les intervalles de température et sur les effets locaux. En conclusion, l'applicabilité de la relation de CC ne doit pas être généralisée quant à l’étude des précipitations extrêmes, il est également important de considérer l'échelle temporelle, la résolution du modèle utilisé et la saison de l'année. L’évolution de cette relation de CC devrait être évaluée avec des simulations à très haute résolution spatiale (version en développement au centre ESCER), et pour d’autres zones climatiques, sachant que les intervalles de températures et les effets locaux exercent un rôle majeur sur les occurrences et les intensités des fortes précipitations. Ces éléments sont essentiels à intégrer dans le contexte des changements climatiques, en raison des conséquences associées aux fortes précipitations, notamment sur l’occurrence des inondations. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Clausius-Clapeyron, évènements extrêmes, aléas météorologiques, risques d’inondation, changements climatiques
Keywords: Gachon_Philippe

Analysis of the Development Mechanisms of a Polar Low over the Norwegian Sea Simulated with the Canadian Regional Climate Model - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (Atmosphere, 2023)
Polar lows (PLs) are maritime mesoscale cyclones associated with severe weather. They develop during marine cold air outbreaks near coastlines and the sea ice edge. Unfortunately, our knowledge about the mechanisms leading to PL development is still incomplete. This study aims to provide a detailed analysis of the development mechanisms of a PL that formed over the Norwegian Sea on 25 March 2019 using the output of a simulation with the sixth version of the Canadian Regional Climate Model (CRCM6/GEM4), a convection-permitting model. First, the life cycle of the PL is described and the vertical wind shear environment is analysed. Then, the horizontal wind divergence and the baroclinic conversion term are computed, and a surface pressure tendency equation is developed. In addition, the roles of atmospheric static stability, latent heat release, and surface heat and moisture fluxes are explored. The results show that the PL developed in a forward-shear environment and that moist baroclinic instability played a major role in its genesis and intensification. Baroclinic instability was initially only present at low levels of the atmosphere, but later extended upward until it reached the mid-troposphere. Whereas the latent heat of condensation and the surface heat fluxes also contributed to the development of the PL, convective available potential energy and barotropic conversion do not seem to have played a major role in its intensification. In conclusion, this study shows that a convection-permitting model simulation is a powerful tool to study the details of the structure of PLs, as well as their development mechanisms.
Keywords: Gachon_Philippe

Polar low developed in the Norwegian Sea on 25 March 2019 – Simulations with the Canadian Regional Climate Model (CRCM6/GEM4) and manual track - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (Borealis, 2023)
This dataset contains: 1. The output of an ensemble of simulations of a polar low that developed over the Norwegian Sea on 25 March 2019. 2. The manually-obtained tracks of the polar low. 1. Simulation output The simulations of the polar low were conducted with the convection-permitting Canadian Regional Climate Model version 6 (CRCM6/GEM4) driven by the reanalysis ERA5. The model has a grid mesh of 0.0225° and a vertical grid with 62 levels. The size of the model domain is 1004 x 1004 grid points, excluding the sponge zone, and the model top is at 2 hPa. The model was initialised every six hours from 23 March at 0000 UTC to 24 March at 1800 UTC, and the end date of the simulations was 26 March at 0600 UTC. This dataset contains the hourly output of these eight simulations. The 2D fields include several variables at screen level (temperature, dewpoint temperature, relative humidity, horizontal wind, wind gust) as well as sea level pressure,1 h accumulated precipitation, and surface sensible and latent heat fluxes. The 3D fields are geopotential height, temperature, relative humidity, horizontal wind, and the vertical velocity in pressure coordinate, and they are provided on 22 pressure levels from 1,000 to 10 hPa. 2. Polar low tracks This dataset contains the different tracks of the polar low that have been obtained using the observations, the reanalysis ERA5 and the output of the eight simulations. The data provided are the time, latitude and longitude of the track points, as well as the sea level pressure minimum. For the track obtained using observations, the dataset also includes the distance between the track point and the closest surface station (which is the one that provides the value of the sea level pressure minimum). Only the sea level pressure observations from stations within 25 km from the PL centre are included.
Keywords: Gachon_Philippe

Assessment of simulations of a polar low with the Canadian Regional Climate Model - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (PLOS ONE, 2023)
Polar lows (PLs), which are intense maritime polar mesoscale cyclones, are associated with severe weather conditions. Due to their small size and rapid development, PL forecasting remains a challenge. Convection-permitting models are adequate to forecast PLs since, compared to coarser models, they provide a better representation of convection as well as surface and near-surface processes. A PL that formed over the Norwegian Sea on 25 March 2019 was simulated using the convection-permitting Canadian Regional Climate Model version 6 (CRCM6/GEM4, using a grid mesh of 2.5 km) driven by the reanalysis ERA5. The objectives of this study were to quantify the impact of the initial conditions on the simulation of the PL, and to assess the skill of the CRCM6/GEM4 at reproducing the PL. The results show that the skill of the CRCM6/GEM4 at reproducing the PL strongly depends on the initial conditions. Although in all simulations the synoptic environment is favourable for PL development, with a strong low-level temperature gradient and an upper-level through, only the low-level atmospheric fields of three of the simulations lead to PL development through baroclinic instability. The two simulations that best captured the PL represent a PL deeper than the observed one, and they show higher temperature mean bias compared to the other simulations, indicating that the ocean surface fluxes may be too strong. In general, ERA5 has more skill than the simulations at reproducing the observed PL, but the CRCM6/GEM4 simulation with initialisation time closer to the genesis time of the PL reproduces quite well small scale features as low-level baroclinic instability during the PL development phase.
Keywords: Gachon_Philippe

Recent advances in polar low research: current knowledge, challenges and future perspectives - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (Tellus A: Dynamic Meteorology and Oceanography, 2021)
Keywords: Gachon_Philippe

Correction to: Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections - Wazneh, Hussein; Gachon, Philippe; Laprise, René; de Vernal, Anne; Tremblay, Bruno (Climate Dynamics, 2021)
The article: Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections, written by Hussein Wazneh, Philippe Gachon, René Laprise, Anne de Vernal, Bruno Tremblay was originally published electronically on the publisher’s internet portal (currently SpringerLink) on 5 January 2021 without open access.
Keywords: Gachon_Philippe

Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections - Wazneh, Hussein; Gachon, Philippe; Laprise, René; de Vernal, Anne; Tremblay, Bruno (Climate Dynamics, 2021)
Atmospheric blockings are generally associated with large-scale high-pressure systems that interrupt west-to-east atmospheric flow in mid and high latitudes. Blockings cause several days of quasi-stationary weather conditions, and therefore can result in monthly or seasonal climate anomalies and extreme weather events on the affected regions. In this paper, the long-term coupled CERA-20C reanalysis data from 1901 to 2010 are used to evaluate the links between blocking events over the North Atlantic north of 35° N, and atmospheric and oceanic modes of climate variability on decadal time scales. This study indicates more frequent and longer lasting blocking events than previous studies using other reanalyses products. A strong relationship was found between North Atlantic blocking events and North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO) and Baffin Island–West Atlantic (BWA) indices, in fall, winter and spring. More blocking events occur during the negative phases of the NAO index and positive phases of the BWA mode. In some situations, the BWA patterns provide clearer links with the North Atlantic blocking occurrence than with the NAO alone. The correlation between the synchronous occurrences of AMO and blocking is generally weak, although it does increase for a lag of about 6–10 years. Convergent cross mapping (CCM) furthermore demonstrates a significant two-way causal effect between blocking occurrences and the NAO and BWA indices. Finally, while we find no significant trends in blocking frequencies over the last 110 years in the Northern Hemisphere, these events become longer lasting in summer and fall, and more intense in spring in the North Atlantic.
Keywords: Gachon_Philippe

Inondations des printemps 2017 et 2019 dans le bassin versant de la rivière des Outaouais (Québec, Canada) : analyse des facteurs physiographiques et météorologiques en cause - Benoit, Clémence; Demers, Isabelle; Roberge, François; Gachon, Philippe; Laprise, René (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Gachon_Philippe